Finite horizon robust synthesis using integral quadratic constraints. (11th February 2021) - Buch, Jyot; Seiler, Peter
Abstract: We present a robust synthesis algorithm for uncertain linear time‐varying (LTV) systems on finite horizons. The uncertain system is described as an interconnection of a known LTV system and a perturbation. The input–output behavior of the perturbation is specified by time‐domain Integral Quadratic Constraints (IQCs). The objective is to synthesize a controller to minimize the worst‐case performance. This leads to a nonconvex optimization. The proposed approach alternates between an LTV synthesis step and an IQC analysis step. Both induced ℒ 2 and terminal Euclidean norm penalties on output are considered for finite horizon performance. The proposed algorithm ensures that the robust performance is nonincreasing at each iteration step. The effectiveness of this method is demonstrated using numerical examples.